Effect Of The Diabetes Exercise On The Blood Sugar Levels In Diabetes Mellitus Patients - Dwi Mustikawati; Erna Erawati; Heru Supriyatno (Universitas Padjadjaran, 2020)
Diabetes is a condition that the pancreas does not produce enough insulin or the body can’ effectively using insulin and its impact on disease complications. Physical exercise is one aspect of the management of diabetes that affects reducing the blood glucose rate. The objective of this research was to find the influence of the diabetes exercise on blood sugar rate at the Public Health Centers Mertoyudan II. This study was a quasiexperimental applying the non-equivalent control group. Respondents were 37 for the intervention group and 37 to the control group. The diabetes exercise performed six times within two weeks. The result found that the paired t-test result with a significance level (α) 95 % was p-value = 0,001. There were significant differences in the decreasing average of the blood sugar rate between the intervention and the control group. Further research is needed by increasing the intervention to become three times per week for 4 weeks’ intervention.